Isolation and characterization of amylolignocellulolytic fungi from sago industrial waste - Siti Nur Hidayah, Bujang (Universiti Malaysia Sarawak, 2011)
Total five fungi isolates were found from sago industrial waste. Screening of the fungi isolates was done by starch agar plate, RBBR dye decolourization and CMC-Congo Red method. One of the isolate was negative for amylase activity and all four isolates were positive for cellulase activity. Only two isolates were positive for ligninase activity and overall screening results showed only two isolates were positive for all three enzymes. Molecular characterization was done and PCR product size between 600 - 750bp was obtained when amplified with ITS primers. Isolate that was positive for amylolignocellulolytic identified as Tinctoporellus sp. Solid State Fermentation (SSF) using sago waste as a substrate was done to analyze enzyme activity. Enzyme activity for amylase, cellulase, lignin peroxidase, manganese peroxidase and laccase were 2.457 umol/min, 19.575 umol/min, 13.352 umol/min, 2.955 umol/min and 23.233 umol/min respectively.